2015
DOI: 10.1007/s40618-015-0330-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of maternal vitamin D status on obstetric well-being

Abstract: Despite its discovery 100 years ago, vitamin D (VD) has emerged as one of the most controversial nutrients and prohormones of the 21st century. In the past few years, a growing interest in VD has been observed in the biomedical literature due to evidences demonstrating a relevant relationship not only between regulation of calcium and phosphorus homeostasis, but also multiple disease states and low VD status in the population. Indeed, several studies carried out to decipher its role in the body in almost every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 71 publications
0
18
0
17
Order By: Relevance
“…Earlier, it was hypothesized that this was due to cold or humidity, but we recently suggested an alternative interpretation that lack of sun exposure might be the environmental factor causing the increased risk of eclampsia (25). Vitamin D deficiency in late pregnancy is related to an increased risk of pre-eclampsia (26). Results from early pregnancy are more heterogeneous (27).…”
Section: The Risk Of All-cause Death Due To Cardiovascular Disease (Cmentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier, it was hypothesized that this was due to cold or humidity, but we recently suggested an alternative interpretation that lack of sun exposure might be the environmental factor causing the increased risk of eclampsia (25). Vitamin D deficiency in late pregnancy is related to an increased risk of pre-eclampsia (26). Results from early pregnancy are more heterogeneous (27).…”
Section: The Risk Of All-cause Death Due To Cardiovascular Disease (Cmentioning
confidence: 96%
“…Vitamin D has an immunomodulatory, antiinflammatory effect and produces antibacterial proteins, and might be involved in the etiology of both preterm birth and infections (26,28). Furthermore, vitamin D deficiency has been associated with fetal growth restriction, a major cause of perinatal death.…”
Section: The Risk Of All-cause Death Due To Cardiovascular Disease (Cmentioning
confidence: 99%
“…Cord blood 25(OH) D concentrations <75 nmol/l have also been linked to infantile wheezing and eczema, possibly due to adverse consequences on the early immune development of the foetus. However, there is still not enough evidence to show whether VD supplementation increases or decreases the risk of allergies, and therefore this requires further exploration (23,48). Re-garding neurocognitive development, while one study found no association between maternal VD status during pregnancy and neurocognitive function, a recent larger-sized study linked maternal serum 25(OH)D levels during pregnancy with language development in the offspring (23,48).…”
Section: Other Impacts Of Maternal Vd Status On the Offspring's Healthmentioning
confidence: 99%
“…68 Myometrial contractility is also dependent on vitamin D-regulated calcium release into muscle, and thus sufficient vitamin D levels could decrease PTB risk by helping maintain myometrial quiescence. 91 With regard to neonatal outcomes, the calcitropic effects of vitamin D are fairly well established. It is known that severe maternal VDD predisposes newborns to neonatal hypocalcaemia and subsequent rickets.…”
Section: Calcitropic Functionsmentioning
confidence: 99%
“…85 First, by impairing the normal Th-1 to Th-2 cytokine balance, VDD leads to increased Th-1 cytokine expression resulting in the excessive inflammation, hypertension, and hampered immunological tolerance for implantation that are characteristic of PE. 91,100 Second, the chronic inflammatory state resulting from these elevated pro-inflammatory cytokines increases risk of developing insulin resistance and GDM. It is also an added risk factor for PTB since it can promote premature membrane rupture and spontaneous labor.…”
Section: Immune Functions Of Vitamin D In Pregnancy and Neonatal Healthmentioning
confidence: 99%